Effects of PDE4 inhibitors on lipopolysaccharide-induced priming of superoxide anion production from human mononuclear cells - Noëlla Germain; Marianne Corbel; Chantal Belleguic; Elisabeth Boichot; Vincent Lagente (Mediators of Inflammation)
Aims: Phosphodiesterase 4 (PDE4) inhibitors have been described as potent anti-inflammatory compounds, involving an increase in intracellular levels of cyclic 3',5'-adenosine monophosphate (AMP). The aim of this study was to compare the effects of selective PDE4 inhibitors, rolipram and RP 73-401 with the cell permeable analogue of cyclic AMP, dibutyryl-cyclic AMP (db-cAMP) and the anti-inflammatory cytokine interleukin-10 (IL-10) on superoxide anion production from peripheral blood mononuclear cells preincubated with lipopolysaccharide (LPS).